The special drills for fatness and their effect in developing some basic skills in basket ball for age ( 17- 18 ) - Abedalsatar, Muhanad; Hanoon, Wasan (Journal of Physical Education, 2009)
The aim from the research is repairing special drills in fatness for young basket ball players in age ( 17- 18 ) and to know the effect of fatness developing for young basket ball players and the effect of fatness developing on some basic skills in young basket ball players . the Iraqi young basket ball players poverty for fatness and that is clear throw the ability of them to control their role in the games by facing the difficult situations and that so effective on his establishments , his role , and his skills . addition to the fatness it doesn't have the wide space or have the big attention to the researchers and trainers so that causes reducing in ( physical and drills level ) . The tow researchers depend on ( 5 ) five physical and skills examinations on the players in al adhmea club ( age 17- 18 ) in year ( 2007 – 2008 ) the number of the players were 12 players . The results were as below :- the shape and topic of the special drills were have big effect on developing fatness in to the young basket ball players . to develop fatness by using variety repeat have positive effect in developing some of basic skills ( attack , defense ) for young basket ball players: basic attack skills ( scoring by jumping from under the basket , dribble by changing turned . basic defends skills ( movement of the defense players